Atraumatic Bone Marrow Edema Involving the Epiphyses - Woertler, Klaus; Neumann, Jan (Seminars in Musculoskeletal Radiology, 2023)
Bone marrow edema (BME)-like signal intensity involving the epiphyses of tubular bones represents a frequent magnetic resonance imaging finding associated with a wide spectrum of bone and joint disorders. It is important to distinguish this finding from cellular infiltration of bone marrow and to be aware of the differential diagnosis of underlying causes. With a general focus on the adult musculoskeletal system, this article reviews the pathophysiology, clinical presentation, histopathology, and imaging findings of nontraumatic conditions associated with epiphyseal BME-like signal intensity: transient bone marrow edema syndrome, subchondral insufficiency fracture, avascular necrosis, osteoarthritis, arthritis, and bone neoplasms.
Keywords: transient bone marrow edema syndrome; subchondral insufficiency fracture; avascular necrosis; osteoarthritis; bone neoplasms